2017
DOI: 10.3390/jcm6020013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which B Cells and Regulatory T Cells Influence Development of Murine Organ-Specific Autoimmune Diseases

Abstract: Experiments with B cell-deficient (B−/−) mice indicate that a number of autoimmune diseases require B cells in addition to T cells for their development. Using B−/− Non-obese diabetic (NOD) and NOD.H-2h4 mice, we demonstrated that development of spontaneous autoimmune thyroiditis (SAT), Sjogren’s syndrome and diabetes do not develop in B−/− mice, whereas all three diseases develop in B cell-positive wild-type (WT) mice. B cells are required early in life, since reconstitution of adult mice with B cells or auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…However, given the observed prognostic interaction between T cells and B cells, future studies should also explore whether such an interaction exists in the predictive setting, and how neoadjuvant chemo- or chemoradiotherapy affects the density and prognostic effects of various subsets of TILs. In addition, the role of B cells in immune checkpoint inhibitor therapy has not yet been fully examined and may be of importance, since it has lately been shown that also T cells can be dependent on B cell activation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given the observed prognostic interaction between T cells and B cells, future studies should also explore whether such an interaction exists in the predictive setting, and how neoadjuvant chemo- or chemoradiotherapy affects the density and prognostic effects of various subsets of TILs. In addition, the role of B cells in immune checkpoint inhibitor therapy has not yet been fully examined and may be of importance, since it has lately been shown that also T cells can be dependent on B cell activation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in PD-1 −/− mice, activation of autoreactive T and B cells is apparently not diminished, because autoimmunity and autoantibody responses are increased after anti-CD40L, even though GCs are effectively depleted. B cells function as important APCs for the development of ATD and pSS (59), suggesting that anti-CD40L does not effectively inhibit T cell/APC and/or B cell activation in PD-1 −/− mice. Effective inhibition by anti-CD40L apparently requires an intact PD-1/PDL pathway, as shown for CD28 −/− mice given anti–PD-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that B cells can affect Treg responses to autoimmune diseases ( 29 32 ). In mouse studies using both genetically B cell-deficient and anti-CD20-treated animals, B cells have been reported to have both positive and negative effects on the size and function of the Treg subset (reviewed in references 33 and 34 ). Some of the differences in experimental outcomes can be attributed to the time during autoimmune disease when the depleting antibodies (Abs) were given, to mouse strain differences (NOD [ 33 ] and BALB/c [ 35 ] mice give results different from those given by C57BL/6 mice), and/or to whether the Tregs induced were peripherally derived or thymus derived.…”
Section: Introductionmentioning
confidence: 99%